MODEL TGT DENGAN CERDAS CERMAT BERKELOMPOK UNTUK MENINGKATKAN KARAKTER DAN PEMECAHAN PERMASALAHAN MATEMATIKA BANGUN RUANG - Diana Setiani; Yuliana; Nughthoh Arfawi Kurdhi (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
Learning becomes less interactive when students are learning to build space because they focus more on the teacher's explanations. Students' mathematical character and problem-solving skills cannot be developed by this learning. An alternative for helping pupils improve their mathematical character and problem-solving skills is the TGT learning approach. The two cycles of this classroom action research project are designed to enhance students' mathematical character and problem-solving skills. Group intelligence was used in conjunction with the TGT model at SMP Negeri 4 Klaten class VIII. Students take a pretest to ascertain their starting abilities before class action starts. With only 3% of pupils completing the pretest, the outcomes were still quite poor. Students' ability to solve mathematical problems improved when they took action.Likewise, students' mathematical character has improved, namely in cycle I only 59% of students have mathematical character in the moderate category, while in cycle II as many as 78% of students have mathematical character in the good category.